Computer skills and internet use in adults aged 50-74 years: influence of hearing difficulties - Henshaw, Helen; Clark, Daniel P.A.; Kang, Sujin; Ferguson, Melanie A. (Journal of Medical Internet Research, 2012)
BACKGROUND